Spatially Programmable Electroadhesive Enables In Situ Site-Selective Functional Coupling - Guo, Yuting (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.